2012
DOI: 10.1589/jpts.24.275
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Cervical Lordosis, Forward Head Posture, Cervical ROM and the Strength and Endurance of the Deep Neck Flexor Muscles in College Students

Abstract: Abstract. [Purpose] This study was conducted in order to examine the correlations between cervical lordosis angles (Absolute Rotation Angle, ARA, forward head posture, FHP, Anterior Weight Bearing, AWB), the range of flexion and extension (RFEM), the strength and endurance of the deep neck flexor (DNF) and cervical pain. [Subjects] The study enrolled 24 university students (female: 12, male:12) aged in their 20s.[Methods] ARA, AWB and RFEM were analyzed using radiographs of lateral views. Strength and endura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 10 publications
(9 reference statements)
1
10
0
1
Order By: Relevance
“…This exercise is known to strengthen deep neck flexors and stretch the upper cervical extensors. Both of these groups of muscles are highly impacted by muscle spindles and their weakness and length imbalance in individuals with forward head posture has been reported by other studies 24 . These muscles are also responsible for the head and cervical stability.…”
Section: Discussionsupporting
confidence: 65%
“…This exercise is known to strengthen deep neck flexors and stretch the upper cervical extensors. Both of these groups of muscles are highly impacted by muscle spindles and their weakness and length imbalance in individuals with forward head posture has been reported by other studies 24 . These muscles are also responsible for the head and cervical stability.…”
Section: Discussionsupporting
confidence: 65%
“…This could be because advanced research targeted selective respiratory accessory muscles, and the period of mediation was longer than that of this study by over 6 weeks. Gong20 ) reported that CVA positively correlates with NDI as a consequence of performing correlation analysis between CVA, the range of motion of deep neck flexors, and NDI using data from 24 normal people. Iqbal9 ) showed improvement of NDI after mediating neck flexion exercises using biofeedback equipment for 4 weeks for 30 teachers complaining of neck pain.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that a larger cervical extension range of motion (ROM) results in a corresponding decrease in forward head posture (FHP) and greater deep neck flexor (DNF) endurance 1) . The cervical extension ROM highly influences our daily lives.…”
Section: Introductionmentioning
confidence: 99%